Potensi Material Nano Dalam Menyerap Gelombang Radar (Stealth) : Revolusi Teknologi Militer - Shafira, Nadia Icha; Aritonang, Sovian (Rekayasa Material, Manufaktur dan Energi, 2025)
The stealth capability in modern defense technology heavily relies on materials that can evade radar detection. Nano-based materials, such as graphene and carbon nanotubes (CNT), have emerged as innovative solutions with superior electromagnetic and physical properties. This study aims to analyze the potential and challenges of using nano materials in stealth technology, highlighting their ability to absorb radar waves through electron resonance interactions and high surface properties. Graphene, with its two-dimensional carbon atomic structure and high conductivity, and CNT, which features a nano-tube structure with exceptional thermal and mechanical properties, have been shown to significantly reduce radar reflection. However, challenges in mass production and material stability under extreme conditions still pose barriers. This study also compares the advantages of nano materials with conventional materials such as ferrite and heavy metals, showing that nano materials are lighter, more flexible, and more efficient. Through a review of current literature, this research reveals that nano materials have the potential to replace or complement conventional stealth materials in future military applications.